2018
DOI: 10.1177/2192568218771911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Cervical Facet Fractures Treated Nonoperatively With Hard Collar or Halo Immobilization

Abstract: Study Design:Retrospective review.Objectives:To evaluate the rate of nonoperative treatment failure for cervical facet fractures while secondarily validating computed tomography–based criteria proposed by Spector et al for identifying risk of failure of nonoperative management.Methods:Single-level or multilevel unilateral cervical facet fractures from 2007 to 2014 were included. Exclusion criteria included spondylolisthesis, dislocated or perched facets, bilateral facet fractures at the same level, floating la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
(38 reference statements)
0
17
0
9
Order By: Relevance
“…For facet fractures with instability (F2), similar inferences can be made given the controversial nature of facet fracture management particularly when unstable. 32 34 Additionally, for other variables in the classification, only the N3 ( P = 0.02) neurological grade showed significant variation across surgeon experience, with variability noted in mid-career surgeons, likely secondary to the aforementioned controversies in the management of incomplete spinal cord injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For facet fractures with instability (F2), similar inferences can be made given the controversial nature of facet fracture management particularly when unstable. 32 34 Additionally, for other variables in the classification, only the N3 ( P = 0.02) neurological grade showed significant variation across surgeon experience, with variability noted in mid-career surgeons, likely secondary to the aforementioned controversies in the management of incomplete spinal cord injuries.…”
Section: Discussionmentioning
confidence: 99%
“… 32 34 Various studies in spine trauma discuss the persistently controversial management of cervical facet fractures, with F3 injuries generally requiring surgical intervention for instability. 32 34 In a recent case series, Manoso et al 32 identified 60 consecutive cases of floating lateral mass cervical facet fractures between C3-C7, and found that all patients treated nonoperatively developed instability, whereas all patients treated with two-level fusions did not show evidence of radiographic failure and maintained alignment. Comparatively, Vedantam et al 33 retrospectively reviewed 35 patients with subaxial cervical facet fractures, six of whom had F3 injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This classification scheme has demonstrated adequate interobserver agreement and intra-observer reproducibility in multiple studies [1,5,[7][8][9]. Even with an ideal classification scheme, significant heterogeneity remains with regard to the work-up and treatment of subaxial unilateral facet fractures [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…This disparity in outcomes has resulted in a lack of consensus-based algorithms for deciding between operative and nonoperative treatments. Within that, the type of immobilization and surgical approach used for nonoperative and operative management, respectively, is a matter of surgeon preference and experience [10,14,19,[21][22][23][24][25]. Computed tomography (CT)-and magnetic resonance imaging (MRI)based criteria for classifying and predicting failure have also been investigated, but controversy ensues regarding the imaging necessary to appropriately work-up facet fractures [12,20].…”
Section: Introductionmentioning
confidence: 99%
“…6 Weight of the patient, comminution of fracture fragments, associated posterior element fracture, height of fracture, and multilevel facet fractures are all predictors of failure of conservative treatment. 6,7 The corollary we can draw from this is that not only is operative intervention mandatory in UFD, one must also look carefully for signs of covert adjacent segment injury like undisplaced facet fractures (which may be a milder form of the contiguous UFD described by Das et al 3 ) and if found would mandate inclusion of more levels in the fixation.…”
Section: Introductionmentioning
confidence: 99%